Identifying Interpersonal Function in Movie "The Pursuit of Happyness": Job Interview Scene through Functional Linguistics - Partohap Saut Raja Sihombing; Chintya Sinambela; Ester Sitorus; Yemima Pangaribuan; Sry Butar-butar; Herman Herman; Suhono Suhono (Anglophile Journal, 2025)
This research aims to classify the interpersonal meaning in “The Pursuit of Happyness” movie scene, job interview scene. This study employs a descriptive-qualitative method to explore the interpersonal meaning in the language used during a job interview scene from the movie "The Pursuit of Happyness." Utilizing Halliday's framework for functional linguistics, the researchers analyzed 82 clauses from the scene, focusing on mood structures, speech functions, and the use of modality. The analysis revealed that statements were the predominant speech function, consistent with the informative nature of job interviews. The study identified various linguistic elements, such as subjects, finites, predicators, complements, and adjuncts, which are crucial in understanding the characters' use of language to convey their identities, intentions, and social dynamics. The findings contribute to the cross-disciplinary understanding of linguistics, film studies, and communication, offering insights into effective communication strategies in professional settings. The research provides a detailed examination of how language is used to negotiate relationships, express personal attitudes, and enact social roles within the high-stakes communicative situation depicted in the film.